The effect of health education through audio-visual media on improving knowledge about breast milk management among working breastfeeding mothers in the working area of the community health centre (puskesmas) Leuwigajah City Cimahi 2023 - Nurhayati, Fitri (Science Midwifery, 2024)
The purpose of this study was to determine the effect of health education through audio-visual media on increasing knowledge about expressed breast milk management in breastfeeding mothers who work in the working area of the Leuwigajah Health Centre, Cimahi City in 2023. The method used was quasi experimental with one group pre test-post test design. The sample of this study was 32 breastfeeding mothers who work in the working area of the Leuwigajah Health Centre, Cimahi City in 2023. Data collection using questionnaires with audio visual media intervention. Univariate and bivariate analyses were conducted with Wilcoxon Sign Rank Test. The results showed that there was an increase in the mean value before (59.78) and after (89.25) was given, and there was an effect of health education through audio visual media on increasing knowledge about dairy milk management in working breastfeeding mothers (p value 0.000). The conclusion of this study shows that there is an effect of health education through audio visual media on increasing knowledge about expressed breast milk management in working breastfeeding mothers in the working area of the Leuwigajah Health Centre, Cimahi City in 2023. Suggestions for midwives, audio-visual media can be used to increase knowledge in working breastfeeding mothers about express milk management.